742-P: Antidrug Antibodies Do Not Impact Pharmacokinetics, Efficacy, and Safety of Tirzepatide: Analysis of Data from 7 Phase 3 Studies - CALDERON, BORIS; MULLINS, GARRETT R.; HODSDON, MICHAEL; LI, GRACE; ANGLIN, GREG; URVA, SHWETA; SCHNECK, KAREN; BARDOS, JENNIFER N.; MARTINS, RICARDO F.; BROWN, KATELYN (Diabetes (New York, N.Y.), 2022)
Tirzepatide (TZP) is a dual glucose-dependent insulinotropic polypeptide (GIP) and glucagon like peptide (GLP) -1 receptor agonist developed for the treatment of type 2 diabetes. Patients receiving TZP may develop an immune response to the 39 amino acid synthetic peptide. This study aimed to evaluate treatment emergent (TE) anti-drug antibodies (ADA) in TZP-treated participants across 7 Phase 3 trials and its potential effect on pharmacokinetics (PK) , efficacy, and safety. A multi-tiered immunogenicity testing strategy was used to detect and characterize ADA. ADA were characterized for their ability to cross react to native GIP (nGIP) and GLP-1 (nGLP-1) , neutralize TZP activity on GIP and GLP-1 receptors, and neutralize nGIP and nGLP-1. ADA were assessed at baseline and throughout the course of the study up to week 40 (SURPASS 1, 2, and 5) or week 52 (SURPASS 3, 4, Japan-mono, and Japan-combo) . Among all ADA-evaluable patients across the Phase 3 trials (N=5025) , TE ADA developed in 51.1% of patients treated with TZP, and the proportions were similar across the 3 TZP dose groups (5, 10, and 15 mg) . At baseline, 7.0% of patients had pre-existing ADA. Maximum ADA titers ranged from 1:20 to 1: 81920 (median 1:160) among TE ADA+ patients. Neutralizing antibodies (NAb) against TZP activity on GIP and GLP-1 receptors were observed in 1.9% and 2.1% of the TE ADA+ patients, respectively. Less than 1.0% of TZP-treated TE ADA+ patients had cross-reactive NAb against nGIP or nGLP-1. TE ADA status, ADA titer, and NAb had no discernible impact on PK profile nor HbA1c effects of TZP. The percentage of TE ADA+ and TE ADA- patients with hypersensitivity reactions was similar. A higher proportion of TE ADA+ patients reported injection site reactions, of which all were nonserious and non-severe, and the vast majority occurred and/or resolved irrespective of TE ADA status or titer level.Overall, immunogenicity was not associated with any impact on TZP PK, efficacy, or safety.